PLANNING AND ANALYSIS YOGYA TEGAL TOSERBA STRUCTURE - Gino Harto Wibowo; Tira Roesdiana (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2019)
The strategic geographical location of Tegal City supports the development of business and services. YOGYA Group is a Supermaket and Department Store company. In building construction there is a structural analysis that is used as a method or system to achieve development as planned.The method used in this research is qualitative method. Literature method by collecting data, studying and identifying.Observation method by conducting a survey to the research location. Adhering to the guidelines of SNI 2847: 2013 (Requirements for structural concrete for buildings), SNI 1727: 2013 (Minimum load for building design and other structures), Guidelines for house planning and building loading (PPURG 1987) and SNI 1726: 2012 (earthquake resistance planning procedures for buildings and non-building structures).This analysis obtained a result of dimension data and the number of beam reinforcement, column, plate and the number of pile needs for the YogyaTegal department store building.Keyword : Analysis, Building, Concrete, SNI, Strategic